As origens históricas do Zaratustra nietzcheano: o espelho de Zaratustra, a correção do mais fatal dos erros e a superação da morte de Deus - Fernandes, Edrisi de Araújo (2003)
Through a careful examination of the relationship between Zoroastrianism and the Western tradition, and a detailed and critical reading of the writings of Nietzsche, this work aims at showing to what extent the character Zarathustra , his discourses and poetical-philosophical thoughts, and related passages from many distinct Nietzschean works, directly or undirectly reflect a philosophy that harvests contributions from the Zoroastrian tradition or its headways (in the Judeo-Greco-Christian tradition, and furthermore in the whole Western philosophical tradition). Supplied with this provisions, and with the interpretation cast upon them, Nietzschean philosophy questions the entire Western tradition of thought, and proposes its replacement by a new attitude towards life. This work also intends to show the way the Nietzschean Zarathustra was built up, in the writings of the German philosopher, together with the idea of making, out of the namesake character of the ancient Iranian prophet (Zarathushtra or Zoroaster, the founder of Zoroastrianism), the herald of that important text that intended to bring the German language to its highest perfection , clumping together, and leading to a prophetic-poetic climax consonant with the meaning of the Earth , Nietzsche s key ideas about the rectification of the most fatal of errors and about the death of God . An elaborate investigation has been pursued after the reasons and manners of the building up of Nietzsche s Zarathustra mirroring its Iranian namesake (sections 1.1 to 1.6), and a survey of the works of Nietzsche has suggested unquestionable relations with the Zoroastrian tradition, mostly through the Jewish, Greek or Christian repercussions of this tradition. These relations have been put in context, in many framings (sections 2.1 to 2.3.2), in the ambit of the most fatal of errors - the - creation of morals in the very occasion of its transposition to metaphysics (Ecce Homo, Why I am a destiny , 3). Through an evaluation of the possible circumstances and repercussions of the death of God , the relations between Nietzsche s writings and Zoroastrian tradition have been investigated (sections 3.1 to 3.7), allowing the understanding of this event as an essential component, and tragic outcome, of the rectification of the most fatal of errors